Tree taxa inventory at Ayer Hitam Forest base-camp - Ibrahim, Faridah Hanum; Abdul Rahim, Abdul Rahman; Lepun, Philip; Mohidin, Ibrahim Edham; Saleh, Mohd Nazre (Universiti Putra Malaysia Press, 2001)
An inventory at the base camp along 6 new trails recorded a total of 86 species of seed plant taxa in 68 genera and 32 families. Of this number 22 timber species, 9 fruit tree species, 3 species with medicinal values and 8 species producing dye and tannins were identified. 6 Peninsular Malaysian endemics are also found here, two being new records for Selangor. This area is useful for teaching and practical training for forestry related and environmental courses.